Eco-efficiency in Portuguese companies of marble sector - Catarino, Justina (2016)
The activities developed within an eco-efficiency project in mineral industries located in the largest area for marble extraction in Portugal, in Alentejo region, in the Estremoz – Borba and Vila Viçosa anticline are presented in this paper. The project was designed to apply the sustainability concept in seven companies of marble extraction and transformation. The adopted strategy used new cleaner production models together with sustainable value (SV) improvement, leading to the rationalization of the industrial process, the involvement of economic agents and the orientation of the management of production processes towards eco-efficiency. The challenge was to have the mineral industry managing efficiently the resources on which the business depends, according to sustainability principles. Different opportunities for improvement, related to the minimization of materials, water and energy use, were identified in the companies. Some proposals mainly related to social improvement and small and medium-sized enterprise competitiveness benefits were also selected and discussed. This approach allows the integration of sustainability at company's and region's levels by combining in the entrepreneurial activity the creation of wealth together with the environment protection and the achieving of social benefits. Highlights: The involvement of different stakeholders in the project (Eco-efficiency in Portuguese companies of marble sector) was positive in the discussion and search of solutions for companies. It is possible to involve marble extraction and processing companies in eco-efficiency improvement towards sustainability. Companies from the marble sector improved environmental and social performance and reduced the costs of their production processes by applying SV methodology.